2000
DOI: 10.1016/s0959-440x(00)00115-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a conserved receptor domain that regulates kinase activity: the cytoplasmic domain of bacterial taxis receptors

Abstract: Many bacteria are motile and use a conserved class of transmembrane sensory receptor to regulate cellular taxis toward an optimal living environment. These conserved receptors are typically stimulated by extracellular signals, but also undergo adaptation via covalent modification at specific sites on their cytoplasmic domains. The function of the cytoplasmic domain is to integrate the extracellular and adaptive signals, and to use this integrated information to regulate an associated histidine kinase. The kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
44
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 66 publications
2
44
0
Order By: Relevance
“…In total, the adaptation subdomain contains approximately 100 residues per subunit, of which 21 residues per subunit are acidic (including the four adaptation site glutamates). Figure 2 summarizes the positions of these acidic residues within a structural model of the adaptation subdomain consistent with the chemically determined structure of the native cytoplasmic domain and the crystallographically determined structure of the signaling subdomain (5,9,18). Table 1 lists the acidic residues and indicates their high degree of conservation (20).…”
mentioning
confidence: 68%
“…In total, the adaptation subdomain contains approximately 100 residues per subunit, of which 21 residues per subunit are acidic (including the four adaptation site glutamates). Figure 2 summarizes the positions of these acidic residues within a structural model of the adaptation subdomain consistent with the chemically determined structure of the native cytoplasmic domain and the crystallographically determined structure of the signaling subdomain (5,9,18). Table 1 lists the acidic residues and indicates their high degree of conservation (20).…”
mentioning
confidence: 68%
“…The basic mechanism in Bacillus subtilis (reviewed by Aizawa et al, 2001) and in Escherichia coli (reviewed by Bourret & Stock, 2002;Bren & Eisenbach, 2000;Falke & Kim, 2000;Falke & Hazelbauer, 2001;Stock & Levit, 2000;Taylor et al, 1999) involves complexes of transmembrane receptors (called methyl-accepting chemotaxis proteins or MCPs), CheA autokinase and CheW coupling protein, which allows the receptors to activate the kinase (Morrison & Parkinson, 1997). The CheA kinase autophosphorylates at the expense of ATP with production of ADP (Garrity & Ordal, 1997;Hess et al, 1988a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The current model of cytoplasmic domain architecture describes the domain as an extended, antiparallel four-helix bundle (4,39,40). This model has been proposed on the basis of evidence from (i) chemical studies, which mapped out the four-helix bundle of the signaling subdomain in the full-length, membrane-bound receptor using a cysteine and disulfide scanning approach (41), and (ii) crystallographic studies, which confirmed the existence of the bundle and provided a high-resolution view of its structure in a water-soluble fragment of the cytoplasmic domain (39).…”
mentioning
confidence: 99%